Surface Pressure Estimates for Pitching Aircraft Model at High Angles-of-attack (Short Communication) - Pashilkar, A. A. (Defence Science Journal, 2002)
The surface pressure on a pitching delta wing aircraft is estimated from the normal force and the pitching moment characteristics. The pressure model is based on parametrising the surface pressure distribution on a simple delta wing. This model is useful as a first approximation of the load distribution on the aircraft wing. Leeward surface pressure distributions computed by this method are presented.